2020
DOI: 10.1371/journal.pone.0236456
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence and determinants of Hepatitis B among a cohort of HIV-infected women of reproductive age in Nigeria

Abstract: Introduction Sub-Saharan Africa houses over two-thirds of the 37 million people living with human immunodeficiency virus (HIV) globally and of this, 5–20% are co-infected with Hepatitis B virus (HBV). This is double jeopardy, especially for women of reproductive age in these settings, who can transmit both viruses vertically as well as horizontally to their children. The objectives of this study were to investigate the prevalence and determinants of HBV among women of reproductive age living with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…Ranges of 2% to 15% prevalence of HBV among pregnant women have been reported in Nigeria [24]. In contrast to our findings on similar research studies carried out in other part of Nigeria, the following reported a high prevalence rate of HBV infection (19.8%), among pregnant women attending antenatal care clinic at Federal Medical Center, Keffi, North-Central Nigeria 16.6% among patients attending a tertiary hospital in Jalingo at Ibadan 16.3% and 14.6% in Bauchi, North-Eastern Nigeria [19,[25][26][27]. A pooled prevalence of 13.6% for adults and 11.5% for children from another study conducted in Nigeria [28].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Ranges of 2% to 15% prevalence of HBV among pregnant women have been reported in Nigeria [24]. In contrast to our findings on similar research studies carried out in other part of Nigeria, the following reported a high prevalence rate of HBV infection (19.8%), among pregnant women attending antenatal care clinic at Federal Medical Center, Keffi, North-Central Nigeria 16.6% among patients attending a tertiary hospital in Jalingo at Ibadan 16.3% and 14.6% in Bauchi, North-Eastern Nigeria [19,[25][26][27]. A pooled prevalence of 13.6% for adults and 11.5% for children from another study conducted in Nigeria [28].…”
Section: Discussioncontrasting
confidence: 81%
“…It has had a negative impact on the prevention, detecting and early treatment of the illness during pregnancy [18]. While few studies on the seroprevalence of HBV infection in pregnancy have been conducted in Nigeria, only a few of them took place in secondary healthcare centres in the country's southern area [19]. Perhaps there is a lack of understanding and information about the subject, particularly in FCTA.…”
Section: Introductionmentioning
confidence: 99%
“…However, this program does not address the virus's transmission risk from infected mothers to their babies. Additionally, more than 40% of Nigerians, including young women of reproductive age, live in poverty and cannot afford the HBV vaccination [22]. Routine screening during pregnancy is another preventive strategy for vertical transmission of HBV and HIV, but it is not commonly practiced in Nigeria due to the high cost of testing [20,21].…”
Section: Introductionmentioning
confidence: 99%